Impact of Alginate Composition: From Bead Mechanical Properties to Encapsulated HepG2/C3A Cell Activities for In Vivo Implantation - Capone, Stephanie H. (Public Library of Science, 2013)
Recently, interest has focused on hepatocytes’ implantation to provide end stage liver failure patients with a temporary support until spontaneous recovery or a suitable donor becomes available. To avoid cell damage and use of an immunosuppressive treatment, hepatic cells could be implanted after encapsulation in a porous biomaterial of bead or capsule shape. The aim of this study was to compare the production and the physical properties of the beads, together with some hepatic cell functions, resulting from the use of different material combinations for cell microencapsulation: alginate alone or combined with type I collagen with or without poly-L-lysine and alginate coatings. Collagen and poly-L-lysine increased the bead mechanical resistance but lowered the mass transfer kinetics of vitamin B12. Proliferation of encapsulated HepG2/C3A cells was shown to be improved in alginate-collagen beads. Finally, when the beads were subcutaneously implanted in mice, the inflammatory response was reduced in the case of alginate mixed with collagen. This in vitro and in vivo study clearly outlines, based on a systematic comparison, the necessity of compromising between material physical properties (mechanical stability and porosity) and cell behavior (viability, proliferation, functionalities) to define optima hepatic cell microencapsulation conditions before implantation.